Redesain Antarmuka Pengguna Situs Web Bimbingan Belajar Sinar Education Menggunakan Metode Design Thinking dan System Usability Scale (SUS) - Desman Dwi Saputra; Andika Hartanta; Akriz Alam Annaba'; Dafa Alfauzi; Garno Garno (Jurnal Kridatama Sains dan Teknologi, 2026)
This study aimed to redesign the mobile user interface of the Sinar Education admin panel, an educational tutoring institution in Tambun Selatan, Bekasi Regency. The existing admin panel displayed desktop-oriented data tables that, when accessed on mobile devices, resulted in truncated columns requiring horizontal scrolling, inconsistent action button placement across pages, and a persistent sidebar consuming screen space. The redesign focused on five main pages: dashboard, admin management, applicant list, student management, and payment management. The study employed Design Thinking through five stages (empathize, define, ideate, prototype, test) combined with System Usability Scale (SUS) evaluation before and after the redesign on 10 administrators. The mean SUS score increased from 53.25 (median 55, OK category) to 81.75 (median 82.5, good to excellent category), an improvement of 28.50 points. The Wilcoxon Signed-Rank Test confirmed that this improvement was statistically significant (W=3, p=0.0098, effect size r=0.89). The greatest improvements were observed in workflow clarity and perceived complexity. This study suggests that card-based layouts replacing columnar tables and hamburger menus replacing persistent sidebars have the potential to improve perceived usability for mobile admin panels in nonformal education contexts. This study measured perceived usability via SUS rather than objective task performance, and generalization of the findings should take this limitation into account